THU0220 An estimation of the prevalence of hypermobility. (1st June 2001) - Gumà, M; Roca, J; Holgado, S; Valls-Roc, M; Casado, E; Forcada, J; Duro, JC; Olive, A; Tena, X
Abstract : Background: Hypermobility is associated with several rheumatic manifestations. The association with SLE is controversial. Objectives: To determine the prevalence of hypermobility in two different populations: a general practitioner (GP) office and out-patients clinic of a referral rheumatology hospital. Methods: 280 patients (193 females, 87 males); mean age 44.7 ± 11.2 were consecutively reviewed in a GP office. 370 patients (233 females, 84 males); mean age 50.5 ± 16.8 were consecutively visited at the out-patients rheumatology clinic. Hypermobility was evaluated following the criteria of Carter-Beighton (hypermobility > 4 points). Results: Hypermobility was present in 42/280 (15%) at the GP office and in 81/317 (25%) in the out patients rheumatology clinic. Conclusion: The prevalence of hypermobility at the GP office and a rheumatology clinic is high. Furthermore it is close to the prevalence of hypermobility in the general population.